PENGARUH VOLUNTARY DISCLOSURE TERHADAP EARNINGS RESPONSE COEFFICIENT - Teguh Gunawan Setyabudi (Jurnal Reviu Akuntansi dan Keuangan, 2018)
This study aims to examine and obtain empirical evidence on the effects of voluntary disclosure of earnings response coefficient. Research conducted at the manufacturing companies listed in Indonesia Stock Exchange. The results showed that the voluntary disclosure significant effect on earnings response coefficient. From the results of the regression analysis, it can be said that the greater voluntary disclosure, the lower the market response on earnings announcements. It is possible that the information voluntarily disclosed by the company are not sufficiently represent the expected future profits of investors, so that the shareholders would prefer to use the information in real income in the financial statements alone. Shareholders are not quite sure use voluntary information in making investment decisions that are not directly responding on the market. Variable quality auditor shown to have a significant effect on earnings response coefficient. Meanwhile, the variable leverage proven no effect on earnings response coefficient.